Rancang Bangun Repeater LoRa Berbasis Ebyte E220-400T22D untuk Memperluas Jangkauan Komunikasi - Setiadi, Chandrasena; Mahfudi, Isa (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
The limited availability of cellular networks in remote areas such as mountain trails and highland regions requires the development of a reliable, low-power, and easily deployable communication system. This study presents the design and implementation of a LoRa repeater based on the Ebyte E220-400T22D module to extend data communication coverage under both line-of-sight and non-line-of-sight conditions. The system utilizes an ESP32 microcontroller that controls two LoRa transceiver modules through a store-and-forward mechanism to retransmit data automatically. Experimental results show that the proposed repeater system effectively increases the communication range under various terrain conditions while maintaining signal stability and transmission reliability. The delay observed in data transmission remains within an acceptable range, confirming that the repeater operates efficiently without significantly affecting system performance. Overall, this work demonstrates that the Ebyte E220-400T22D-based LoRa repeater provides a practical and energy-efficient solution for long-range wireless communication in areas with limited telecommunication infrastructure.